Kesulitan Belajar Ekonomi Dalam Perspektif KeterampilanMengajar Guru Dan Motivasi Belajar Pada Siswa Kelas XISMA Muhammadiyah 1 SurakartaTahun Ajaran 2016/2017 - Marlina, Marlina, Drs. Budi Sutrisno, M.Pd (2016)
The purpose of this study was to determine: 1. Learning disabilities according to the teachers' teaching skills. 2. Learning disabilities according to the motivation to learn.3.Learning disabilities according to the teachers' teaching skills andmotivationtolearn. This type of research is use descriptive quantitative . The population in this study were 205 students of class XI SMA Muhammadiyah 1 Surakarta with a sample of 131 students were taken by proportional random sampling technique. The data collection technique using questionnaires that have been tested by validity and reliability testing. Data analysis technique used is a two-wayanalysisofvariance. Based on the analysis and discussion can be concluded, 1) Results of ANOVA analysis of learning difficulties according to teachers' teaching skills obtained calculation shows the calculation of ANOVA Fhitung 0,455 and the probability is 0.501, while Ftabel 3.932. Then the probability of> 0.05 or 0.501> 0.05. H0, which means there is no difference in learning difficulties according to teachers' teaching skills. 2) Results of ANOVA analysis of learning difficulties in learning motivation Fhitung shows the calculated probability of 4.713 and 0.011, while Ftabel 3,083. Then the probability of> 0.05 or 0.011> 0.05 H0 is rejected, that there are differences in learning disabilities according to the motivation to learn. 3) Results of ANOVA analysis of learning difficulties according to teachers' teaching skills and learning motivation showed didapatkanbahwa Fhitung ANOVA calculation is 0.069 with a probability of 1.789, while Ftabel 3,083. Then the probability of> 0.05 or 0.184> 0.05 H0, which means there is no difference in learning difficulties according to teachers'teachingskillsandmotivationtolearn.